PENINGKATAN MUTU GURU MELALUI PELATIHAN PEMBUATAN VIDEO BAHAN PEMBELAJARAN BERBASIS OPEN BROADCASTER SOFTWARE - Aris Suryadi; SC Abadi; Mindit Eriyadi; Dani Usman; YM Hamdani (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2021)
Learning media provided by a teacher to students are generally conventional. This has resulted in a perceived saturation and of course the quality of teachers is seen as low in their eyes. Lack of teacher knowledge in the use of computer applications for creating technology-based learning media. The solution to these problems can be through the provision of training by using the open broadcaster software application as a learning medium. The application is in the form of software that can be downloaded directly on the internet, of course it can be applied by teachers. The target to be achieved in the subject they are teaching. The findings in this activity received a positive and enthusiastic response from the teachers 100%, both the training materials that were delivered, and the activities in operating the application 90%